Pelaksanaan Pembelajaran Sejarah Menggunakan Model Pembelajaran Kooperatif Tipe Jigsaw di SMA Pembangunan Bukittinggi - Raja Difarell Antang Calista; Ridho Bayu Yefterson (Jurusan Sejarah FIS UNP, 2022)
Abstract The selection of learning models is a strategy used by teachers in increasing student learning motivation. The jigsaw-type cooperative learning model is a student-oriented learning model to increase student activity, critical thinking ability, creativity and student responsibility. Therefore, history teachers at Development High School use a Jigsaw-type Cooperative model to make learning more effective and efficient to support the success of history learning. The purpose of this study is to describe the implementation of history learning using a jigsaw-type cooperative model in terms of planning, implementing and evaluating carried out by history teachers of SMA Pembangunan Bukittinggi. The results showed that in planning history teachers compiled learning tools in accordance with the 2013 curriculum reference. Learning tools that include the syllabus, rpp are compiled by the history teacher himself, because according to the teacher, the self-compiled device will be more able to develop competencies that are in accordance with the conditions, maturity, needs of students and the conditions and situations of the classroom and school. In the implementation of history learning using the jigsaw model, it already refers to good learning, this can be seen in the selection of materials, learning methods and media used, as well as the involvement of all students in learning. at the time the learning takes place. Evaluation of learning is carried out during the teacher's learning process, not only assessing from the cognitive realm but also the affective and psychomotor realms of students. Keyword: Planning, Implementation, Evaluation, Jigsaw, History Learning Abstrak Pemilihan model pembelajaran merupakan strategi yang digunakan oleh guru dalam meningkatkan motivasi belajar siswa. Model pembelajaran kooperatif tipe jigsaw merupakan model pembelajaran yang berorientasi kepada siswa untuk meningkatkan keaktifan siswa, kemampuan berpikir kritis, kreativitas serta tanggung jawab siswa. Oleh karena itu, guru sejarah di SMA Pembangunan menggunakan model Kooperatif tipe Jigsaw agar pembelajaran lebih efektif dan efisien untuk mendukung kesuksesan dalam pembelajaran sejarah. Penelitian ini bertujuan untuk mendeskripsikan bagaimana pendidikan sejarah dilaksanakan menggunakan model kooperatif tipe jigsaw dilihat dari perencanaan, pelaksanaan serta evaluasi yang dilakukan oleh guru sejarah SMA Pembangunan Bukittinggi. Hasil penelitian menunjukkan dalam melakukan perencanaan guru sejarah menyusun perangkat pembelajaran sesuai dengan acuan kurikulum 2013. Perangkat pembelajaran yang meliputi silabus, rpp disusun oleh guru sejarah sendiri, karena menurut guru perangkat yang dirancang secara mandiri akan mampu menciptakan kemampuan sesuai dengan situasi, perkembangan, kebutuhan siswa dan situasi serta realitas kelas dan sekolah. Pelaksanaan pembelajaran sejarah dengan model jigsaw sudah mengacu pada pembelajaran yang baik, hal ini terlihat pada pemilihan materi, metode dan media pembelajaran yang digunakan, serta keterlibatan seluruh siswa dalam pembelajaran. pada saat pembelajaran berlangsung. Evaluasi pembelajaran dilakukan selama proses pembelajaran guru tidak hanya menilai dari ranah kognitif saja namun ranah afektif dan psikomotor siswa juga dilakukan oleh guru. Kata Kunci: Perencanaan, Pelaksanaan, Evaluasi, Jigsaw, Pembelajaran Sejarah